Efficacy of Dexamethasone as a Complementary Therapy in Acute Bacterial Meningitis Due to Streptococcus pneumoniae in adults - Moreida Quintero Villalobos; Olmedo Ferrer Ocando; Yenny Ferrer Ocando; María Vizcaíno; Liliam Gonzáles (Universidad del Zulia,Facultad de Medicina,Departamento de Enfermedades Infecciosas y Tropicales, 2006)
Acute bacterial meningitis due to S. pneumoniae in adults has a high morbidity rate. Corticosteroids are not used routinely. Here, complementary therapy with dexamethasona was used in 6 patients who received penicillin plus chloramphenicol. The results showed there was clinical improvement. The continuation of this study with more patients is recommended.